Elevation-dependent warming of land surface temperatures in the Andes assessed using MODIS LST time series (2000–2017) - Aguilar-Lome, Jaime (2019)
This work was supported by FONDECYT through the project: “Monitoreo de la dinámica de fenómenos ambientales y climáticos extremos en el Perú usando la teledetección por satélite”, funded by USAID through the PEER Project: “Strengthening resilience of Andean river basin headwaters facing global change” (PGA-084063) and “AGUA-ANDES: Ecological Infrastructure Strategies for Enhancing Water Sustainability in the Semi-Arid Andes” (PGA-174194), as well as by CONDESAN through the Project: “Investigación sobre una relación de dependencia entre la tasa de cambio de temperatura y la altitud”. JCE received partial support of the AMANECER project funded by the MOPGA program of the French Government. Additionally, we extend our gratitude to the National Meteorology and Hydrology Service of Peru (SENAMHI-Peru) for providing data used in this study. Finally, the authors are grateful to Nicole Chabaneix and to the anonymous reviewers for their contribution to improve this paper.